Uji Efektivitas Beberapa Warna Perangkap terhadap Populasi Lalat Buah Bactrocera sp. (Diptera: Tephritidae) pada Tanaman Cabai Merah - Amirullah, Johanes; Wati, Cheppy (Seminar Nasional Lahan Suboptimal, 2018)
Amirullah et al, 2019. Effectiveness Test of Some Colours Trap on Fruit Fly Population Bactrocera SP. (Diptera: Tephritidae) at Red Chili Plants. pp. 482-487.The aim of this research was to know the effectiveness some colors trap on fruit fly population Bactrocera SP. (Diptera:Tephritidae) at red chili plants. This research was conducted during one period planted from December 2017 until January 2018. Location of research implemented in land the optimization at POLBANGTAN Manokwari in Manokwari West Papua Province. The kind of research was an experimental using a randomized block design (RAK) with 5 treatments and 3 replications. The treatments used are P = Treatment control with a modified trap without color, P1= Treatment with a modified trap yellow color, P2= Treatment with a modified trap red color, P3= Treatment with a modified trap blue color, P4= Treatment with a modified trap green color. The results showed that trap with yellow color can capture most fruit fly population equal to 46 tails and the lowest is red color trap equal to 14 tails. So the best treatment is the fruit fly trap with a modification yellow.